Pengaruh Work Life Balance dan Keterlibatan Kerja Terhadap Kesejahteraan Subjektif (Studi Pada Kantor Komando Distrik Militer 0733/Kota Semarang) - Permata , Erykha; Fauzan, Mohammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study explains the influence of work-life balance and work enggagment on the subjective personal well-being of Army Soldiers in Military District Command 0733/Semarang City. This research uses this type of research (explanatory research). The study population was all Army personnel in the Military District Command 0733 / Semarang City as many as 100 TNI AD personnel were used as sampled (census method). Questioner data collection was carried out using a google form application wich wa sent to respondents. For the purposes of data analysis, Instrument Test is carried out; and Hypothesis Testing and data processing using SPSS. Research findings show that (1) Work Life Balance has a positive and significant effect on subjective well-being; (2) Work Engagement has a positive and significant effect on subjective well-being.